Pengaruh Model Problem Based Learning Berbantuan LKPD Digital terhadap Hasil Belajar Siswa Kelas VIII - Dayulia, Hilmayana Irma; Hikmah, Nurul; Junaidi, Junaidi (Griya Journal of Mathematics Education and Application, 2025)
This study aims to determine the effect of the application of the Problem Based Learning model assisted by digital LKPD on the learning outcomes of eighth-grade students. The method used in this study is a quasi-experimental design with a posttest-only control nonequivalent group design. The population in this study was 113 students with a sample of 45 students. In the experimental group, the Problem Based Learning model was used, while in the control group, the direct learning model was used. The research instruments included observation sheets and mathematics learning outcome tests. The results of data analysis using the t-test showed that the value of , so was rejected. This means that there is a difference in the average student learning outcomes between the experimental group and the control group, where the average posttest score in the experimental group was 70.22 which was higher than the control group of 55.00. Thus, it can be concluded that there is an effect of the Problem Based Learning model assisted by digital LKPD on the learning outcomes of eighth-grade students.